Grazing management as a means of regulating spittlebug (Homoptera: Cercopidae) numbers in central Brasil - Hewitt, George B. (Pesquisa Agropecuaria Brasileira, 2014)
Short duration, high intensity grazing was evaluated as a method of reducing spittlebug numbers in central Brazil. Intense grazing pressure during the nymphal period resulted in a temporary reduction in nymphal density but additional hatching of eggs allowed the density to increase. Intense grazing during the last generation of adults, prior to the start of the dry season drastically reduced the nymphal population. Grazing by cattle in general provided an unsuitable habitat for spittlebug egg survival as both grass height and plant cover decreased under all grazing treatments. In heavily infested pastures (> 20 nymphs/m2) it is recommended to graze the grass short (< 10 cm) during the last generation of adults (April-July) in order to discourage oviposition by adults laying diapause eggs and to expose eggs to detrimental conditions during the dry season. In pastures with low spittlebug density (< 20 nymphs/m2) it is recommended to maintain the forage height at 15 cm - 20 cm during the rainy season for maximum production and efficient use of the forage resource.